Advanced strategies for production of soy-processing enzyme - Islam, S. M. Mahfuzul; Ju, Lu-Kwang (Frontiers in Bioengineering and Biotechnology, 2023)
Enzyme production is critical and often costly for biorefinery. It is challenging to produce enzymes not only with high titers but also proper combinations of all required activities in a single fermentation. Hydrolyzing the 30-35% carbohydrate in soybean meal to sugars can generate high-value protein-rich products and a hydrolysate as fermentation feedstock. However, soy carbohydrate is complex, requiring multiple activities to hydrolyze. Soybean hull (SH) is cheap and can induce production of all necessary carbohydrases by selected Aspergillus niger. Here fermentation strategies of fed-batch SH addition and programmed pH-decrease rates were studied to optimize enzyme productivity and composition. Surprisingly, fed-batch SH addition, originally thought to sustain substrate-inducer availability and reduce feedback repression by sugars, did not increase pectinase and cellulase production significantly and even lowered the α-galactosidase production, when compared with batch fermentation having the same total SH amount (all added initially). On the other hand, the pH-decrease rate could be effectively optimized for production of complex enzyme mixtures. The best fermentation was programmed to lower pH from 7 to 4 in 84 h, at a drop rate of 0.0357 per h. It produced the highest pectinase (19.1 ± 0.04 U/mL), α-galactosidase (15.7 ± 0.4 U/mL), and cellulase (0.88 ± 0.06 FPU/mL). Producing these high enzyme activities in a single fermentation significantly improves the effectiveness and economics of enzymatic soy processing.